1995
DOI: 10.1002/j.1460-2075.1995.tb06983.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodic cdc25C transcription is mediated by a novel cell cycle-regulated repressor element (CDE).

Abstract: We show that the cell cycle‐regulated transcription of the TATA‐less cdc25C gene in late S/G2 is largely mediated by a novel promoter element (CDE) located directly 5′ to one of the two major transcription initiation sites. Genomic dimethylsulfate footprinting experiments, using either synchronized or sorted normally cycling cells, show the formation in vivo of a CDE‐protein complex in both G0 and G1 cells and its dissociation in G2. Mutation of the CDE severely impairs cell cycle regulation of the cdc25C prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
90
1

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 53 publications
3
90
1
Order By: Relevance
“…This procedure yielded almost pure fractions of G 1 and G 2 cells (Figure 1). As previously reported (Lucibello et al, 1995), the CDE in cdc25C promoter was protected in WI38 cells in the G 1 phase, and this occupation is lost in G 2 (see insert in Figure 2). By contrast, in WI38VA13 cells the cdc25C CDE was unprotected in both G 1 and G 2 , although the interactions with constitutively bound NF-Y in the upstream region were una ected by expression of SV40 large T (Figure 2).…”
supporting
confidence: 87%
See 4 more Smart Citations
“…This procedure yielded almost pure fractions of G 1 and G 2 cells (Figure 1). As previously reported (Lucibello et al, 1995), the CDE in cdc25C promoter was protected in WI38 cells in the G 1 phase, and this occupation is lost in G 2 (see insert in Figure 2). By contrast, in WI38VA13 cells the cdc25C CDE was unprotected in both G 1 and G 2 , although the interactions with constitutively bound NF-Y in the upstream region were una ected by expression of SV40 large T (Figure 2).…”
supporting
confidence: 87%
“…The increase in the normally cycling cells is presumably due to an e ect on the G 1 fraction (*60% of the cell population) where CDF-1 is active. Only a marginal e ect of SV-LT was seen with a reporter plasmid containing a mutated CDE (Lucibello et al, 1995;Zwicker et al, 1995b) (data not shown), indicating that CDF-1 is an essential target in the deregulation of the cdc25C promoter by the viral oncoprotein.…”
mentioning
confidence: 93%
See 3 more Smart Citations